Cost containment and competitive tendering for support services in health care system of Jamaica: research paper - Lalta, Stanley (The author [Mona]JA, 1993)
Reviews the theoretical literature on competition tendering (CT) and contracting out. Examines the comparative experience of CT in some developed and developing countries. Evaluates the policy and practice of CT in the hospital support services in Jamaica.